Metode Klasikal Individual dan Kemampuan Membaca Al-Qur'an: Studi Kasus TPQ Nur Iman Banjarejo Pagelaran - Zainal Mustofa; Sita Acetylena (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to describe the implementation of the classical-individual learning method at TPQ Nur Iman Banjarejo Pagelaran, identify its supporting and inhibiting factors, and analyze its implications for santri's Qur'an reading ability. The study employs a descriptive qualitative approach with a case study design. Primary data were obtained through observation of the learning process and in-depth interviews with the TPQ head, ustaz/ustazah, santri, and their parents, complemented by secondary data from administrative documents and santri achievement records. Data were analyzed through data reduction, data display, and conclusion drawing, with validity checked through source, technique, and time triangulation. The findings show that the classical-individual method is carried out in three stages: classical instruction for delivering material collectively, individual instruction through a read-and-listen technique for personal correction, and daily evaluation covering reading etiquette alongside fluency, articulation points, and tajwid. Supporting factors include teacher competence, a systematic method, santri motivation, parental support, and a conducive learning environment, while inhibiting factors include varying santri abilities, limited instructional time, a less-than-ideal teacher-santri ratio, and inconsistent attendance, with a similar pattern of constraints also found at other Qur'anic education institutions. This classical-individual structure is consistent with patterns found in the Tilawati, Qiraati, Ummi, and Usmani methods. It aligns with both the sorogan-bandongan tradition rooted in pesantren education and the principle of stepwise mastery in modern educational theory, indicating that success depends on the consistency of individual correction and the quality of teacher-santri interaction rather than on the method's name alone. Keywords: Case Study, Classical-Individual Method, Qur'an Reading Ability, Supporting and Inhibiting Factors, TPQ